Primer extension coupled with fragment analysis for rapid and quantitative evaluation of 5.8S rRNA isoforms - Venturi, Giulia; Zacchini, Federico; Vaccari, Cinzia Lucia; Trerè, Davide; Montanaro, Lorenzo (PLOS ONE, 2021)
The ribosomal RNA 5.8S is one of the four rRNAs that constitute ribosomes. In human cells, like in all eukaryotes, it derives from the extensive processing of a long precursor containing the sequence of 18S, 5.8S and 28S rRNAs. It has been confirmed also in human cells the presence of three isoforms of 5.8S rRNA: one more abundant called 5.8S short, one called 5.8S long bearing 5 extra-nucleotides at its 5’ end and one 10 nucleotide shorter called 5.8S cropped. So far, little is known about 5.8S long specific role in cell biology and its function in human pathology. The lack of studies on the three 5.8S isoforms could be due to the techniques usually applied to study ribosome biogenesis, such as Northern blot with radioactively labelled probes, that require strict protective measures, and abundant and high-quality samples. To overcome this issue, we optimized a method that combines primer extension with a fluorescently labeled reverse primer designed on the 3’ of 5.8S rRNA sequence and fragment analysis. The resulting electropherogram shows the peaks corresponding to the three isoforms of 5.8S rRNA. The estimation of the area underneath the peaks allows to directly quantify the isoforms and to express their relative abundance. The relative abundance of 5.8S long and 5.8S short remains constant using scalar dilution of RNA and in samples subjected to partial degradation. 5.8S cropped abundance varies significantly in lower concentrate RNA samples. This method allows to analyze rapidly and safely the abundance of 5.8S rRNA isoforms in samples that have been so far considered not suitable such as poorly concentrated samples, RNA derived from frozen tissue or unique samples.